Psychometric Properties of Interpersonal Communication skills Questionnaire (ISAQ) from the Viewpoint of Students at Tabriz University and Tabriz University of Medical Sciences - Firoz Mahmoodi; Zahra Samadi; Zeinab Fizolahzadeh (Journal of Medical Education Development, 2017)
Background and Objective: One of the skills needed for social life is interpersonal communication skills. Assessing the Interpersonal communication skills due to the growth and development of social networks is very important. This study aimed to validate the Fetro's (2000) interpersonal communication skills questionnaire among students of Tabriz University and Tabriz University of Medical Sciences.